IMPACT OF INFORMATION TECHNOLOGY (IT) ON SOCIETY - Gowda B S, Krishne (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Information technology (IT), as defined by the Information Technology Association of America (ITAA), is "the study, design, development, implementation, support or management of computer-based information systems, particularly software applications and computer hardware." IT deals with the use of electronic computers and computer software to convert, store, protect, process, transmit, and securely retrieve information. Information technology (IT) is playing a crucial role in contemporary society. It has transformed the whole world into a global village with a global economy, which is increasingly dependent on the creative management and distribution of information. Globalization of world economies has greatly enhanced the values of information to business organizations and has offered new business opportunities. This paper intended to highlight the Impact of Information Technology (IT) on Society. This paper concludes that the Government of India has been working gradually and successfully towards improving the IT policy climate in the country.